Experiences and Evidence Related to the Learning Outcomes: A Descriptive Study (Proceedings of the International Conference on Education, 2020)
The descriptive study presented here is placed in the context of Higher education. As part of the curriculum transition of the Academic programs of a private University in Mexico City, which went from a model by objectives to learning outcomes, the questions that guided this investigation where: What experiences and evidence scuttled teachers from the operational program of the bachelor´s degree in Education? How do they align to the egress profile set out in the oficial curriculum? Therefore aims to identify and describe the characteristics that define the experiences and evidence proposed by teachers to demonstrate students learning and how they line up with the established egress profile in the official curriculum of the Education program. Among the preliminary findings, it was found that there is no conceptual clarity that distinguishes the experience of learning evidence in the programmatic proposal of the disciplinary syllabus, nor of its articulation with the egress profile. It was also identified that learning experiences and evidence tend to be mostly focused on the figure of the teacher rather than the student.
Keywords: Experiences; evidence; learning outcomes; graduate student profile; programs